Adoption of Bio-pesticide among the Farmers through Internet Usage in Junagadh District of Gujarat - Pithiya, K. N.; Maheta, H. Y.; Kumar, Kalpesh; Bharodia, C. R. (International Journal of Bio-resource and Stress Management, 2024)
This study was conducted during the month of January, 2024 to June, 2024 at Junagadh district of Gujarat. The pivotal measure for reducing pollution and facilitating green and sustainable agriculture lies in the application of biopesticides to replace chemical pesticides. The argument still rests on whether the use of the internet can assist farmers in selecting biopesticides or not. Junagadh district of Gujarat was selected for the study due to its prominent agricultural sector and the pressing need to improve biopesticide selection among local farmers. Total 160 farmers was selected for the study purpose. Probit model was applied in this article to probe the influencing factors regarding the use of the Internet on their selection of the biopesticides by farmers, and the TAM-PR model was also adopted to explore its intrinsic mechanisms. According to the research findings, the use of the Internet directly contributed to the application of biopesticides, which can affect farmers’ decisions regarding biopesticides by means of perceived usefulness and perceived ease of use in an indirect manner. The result regarding perceived risk was not significant. It has a remarkable positive effect on farmers with high academic qualifications compared with those with low academic qualifications. Hence, it is of great significance to continuously facilitate the application of rural Internet usage, encourage environmentally friendly modes of production, and reduce agricultural pollution.